Payment of Participants with Disability in Research: A Scoping Review and Framework - Jennifer Smith-Merry; Damian Mellifont (Social Sciences, 2025)
Payment of people participating in research is a common practice in research. Research ethics guidelines often require additional scrutiny of payment practices and research practices more generally for groups identified as vulnerable, including people with disability. However, the existing guidelines are vague, and often conflict, meaning that it is difficult for researchers to determine what is appropriate in relation to the payment of participants in research. This situation is addressed in this paper, which provides a review of the existing research on the topic of payment of participants considered ‘vulnerable’ in research. We followed a systematic approach to our scoping review, thematically analysed the data identified and reported our results according to the PRISMA-ScR guide for scoping reviews. Fifteen papers met the inclusion criteria and were included in this review. Where studies included empirical findings, most studies were based in the US and Canada, with a small number from European, African, and Asian countries. The key ethical concepts identified in the papers were consent, justice, and reciprocity, which were positioned in relation to coercion and concerns about undue influence from payment. The papers consistently identified economic precarity as being a shared factor across the groups identified as vulnerable which placed them at risk of coercion in relation to payment. The papers also strongly identified context as being an important consideration in both mitigating and enhancing risks around the payment of participants. A framework for considering the payment of participants is offered which responds to the areas identified in the papers. It focuses on the research environment, research situation, participant group, risks and benefits of the research, individual context, relational context, and research practices. This framework is provided as a resource for researchers considering the payment of people with disability in research, and those identified as vulnerable in research more broadly.